2022
DOI: 10.1021/acsaelm.2c00258
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Organic–Inorganic Perovskite Semiconductor-Based High-Flux Neutron Detector with BN Converter

Abstract: Neutrons are analyzed in various fields such as space exploration, neutron radiography, and medicine. When neutrons are employed, a neutron detector is required to control the exposure dose. However, issues such as detector radiation tolerance, response linearity, and γ-ray noise limit the development of effective neutron detectors. Metal halide perovskite based direct conversion radiation detectors exhibit attractive characteristics such as being solution-processable at low temperatures and possessing tunable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…For example, a layer of neutron capture isotopes ( 6 Li, 10 B) was coated on the surface of charged particle detectors, or the isotopes were loaded into bulk scintillators made of glass or plastic materials. [12][13][14][15][16][17] Further, 6 Li and 10 B based compound devices or scintillators such as Cs 2 LiYCl 6 :Ce and 6 LiInP 2 Se 6 have been developed. [18][19][20] In addition, the applications such as nuclear power plants and oil wells require thermal neutron detectors working in harsh radiation environments with high radiation exposure or high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a layer of neutron capture isotopes ( 6 Li, 10 B) was coated on the surface of charged particle detectors, or the isotopes were loaded into bulk scintillators made of glass or plastic materials. [12][13][14][15][16][17] Further, 6 Li and 10 B based compound devices or scintillators such as Cs 2 LiYCl 6 :Ce and 6 LiInP 2 Se 6 have been developed. [18][19][20] In addition, the applications such as nuclear power plants and oil wells require thermal neutron detectors working in harsh radiation environments with high radiation exposure or high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the combination of MHPs with 10 B for thermal neutron detection has been explored and shown to offer significant advantages due to MHPs' excellent optoelectronic properties and 10 B's high neutron capture capability [38][39][40][41][42]. In our work, we propose a bi-layer structure consisting of a 10 B layer and a CsPbBr 3 -based film, created using laser ablation (LA) deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Metal halide perovskites (MHPs) have attracted increasing interest in radiation detection in recent years, as this type of material has good carrier transport properties, large stopping power, low fabrication costs, and high radiation tolerance. , To date, the detectors based on MHPs have been realized to detect X-, γ-, and β-rays, alpha particles, and neutrons, and some of these studies have shown the high radiation tolerance of the detectors. For instance, the performance of the perovskite γ-ray detector reported by Wei et al showed no appreciable degradation after a high accumulated irradiation dose of 350 Gy (about 3.5 million chest X-ray exams) . On a separate note, the perovskite materials were also assessed for the proton radiation tolerance in solar cell structures.…”
Section: Introductionmentioning
confidence: 99%